Magnetic resonance imaging in assessment of liver lesions in patients with extrahepatic primary cancer - Mohson, Khaleel I. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Liver imaging is commonly undertaken in patients with cancer history because, after lymph nodes, the liver is the most frequently involved organ by metastases Objectives: The aim of the study was to evaluate the role of liver MRI (magnetic resonance imaging) in characterization and detection of liver lesion in patients with extrahepatic primary Methods: this is a cross sectional study of 70 patients with extrahepatic liver primary cancer who had their treatment in oncology teaching hospital underwent routine abdominal ultrasound to detect liver lesion(s) and suspicious cases then referred to MRI which was done in Ghazi Alharri and oncology teaching hospital from the period from 1st of September 2015 to end of November 2016, the patients age range from 31 to 75 years Results: hemangioma is the most common solitary liver lesion in patients with extrahepatic primary cancer which represent 27% of lesions detected followed by simple cyst which represent 13% of the lesions, in another hand solitary metastasis seen in 7% of solitary lesions while metastasis is the leading cause behind multiple hepatic lesions and represent about 38% of lesions seen ,unlike solitary lesions, hemangioma is a rare cause and seen in 7% of cases Conclusion: MRI is a required adjuvant tool in evaluation of suspicious liver lesion ,its value was illustrated in characterization and diagnosis of liver lesions depending on their appearance in T1 ,T2 and fat suppression T2 sequences in addition to assess their enhancement pattern after dynamic IV( intravenous) contrast injection. الخلفية: يتم عمل تصوير الكبد عادة للمرضى الذين يعانون من السرطان، لأنه العضو الأكثر اصبابة بانتشار السرطان بعد العقد الليمفاوية. المقدمة: الهدف من هذه الدراسة هو تقييم دور تصوير الكبد بالرنين المغناطيسي في كشفو توصيف افات الكبد في المرضى الذين يعانون من سرطان اولي خارج الكبد. المرضى والطرق: هذة هي دراسة مقطعية ل 70 مريضا يعانون من سرطان اولي خارج الكبد والذين كان علاجهم في مستشفى الأورام التعليمي في مدينة الطب ثم خضعوا لفحص الرنين المغناطيسي في مستشفى الشهيد غازي الحريري ومستشفى الأورام خلال الفترة من 1 سبتمبر 2015 إلى نهاية نوفمبر 2016 وهم من الفئة العمرية بين 31-75 عاما. النتائج: يمثل الورم وعائي الدموي الأكثر شيوعا من الاورام الانفرادية في الكبد في المرضى الذين يعانون من سرطان خارج الكبد والتي تمثل 27٪ من الآفات اكتشفت يليه كيس بسيط والذي يمثل 13٪ من الآفات الانفرادية المكتشفة، من جهة أخرى انتشار الورم الاولي الوحيد يمثل 7٪ من الآفات الانفرادية، والعكس تماما حيث يكون السبب الرائد وراء الآفات الكبدية المتعددة ويمثل حوالي 38٪ من آفة الكبدد المتعددة ، في حين اخر ان الأورام الوعائية تمثل 7٪ من الحالات المتعددة. الاستنتاجات: الرنين المغناطيسي هو أداة مساعدة ومطلوبة في تقييم الآفة الكبد المشبوهة، وتتجلى قيمته في توصيف وتشخيص آفات الكبد اعتمادا على مظهرهم في مقاطعT1 ، T2، ومقاطع T2قمع الدهون بالإضافة إلى تقييم نمط اخذها للصبغة بعد الحقن في الوريد والذي يسمي بالفحص الديناميكي .